Alterations in antioxidant defense system of workers chronically exposed to arsenic, cadmium and mercury from coal flying ash - Zeneli, Lulzim; Sekovanić, Ankica; Ajvazi, Majlinda; Kurti, Leonard; Daci, Nexhat (Environmental geochemistry and health, 2016)
Humans are exposed to different stress factors that are responsible for over-production of reactive oxygen species. Exposure to heavy metals is one of these factors. The aim of the study was to analyze the effect of chronic exposure to heavy metals through coal flying ash on the efficiency of antioxidative defensive mechanisms, represented by the activity of superoxide dismutase, glutathione peroxidase and ascorbic acid. Nonessential elements such as arsenic and mercury levels showed a significant increase ( p > 0.001) in the power plant workers rather than in the control subjects. There were no significant differences of blood cadmium between power plant workers and control subjects. We found a significant positive correlation ( p < 0.05) between BAs/SZn ( r = 0.211), BAs/BSe ( r = 0.287), BCd/SCu ( r = 0.32) and BHg/BSe ( r = 0.263) in the plant workers. Red blood cell antioxidant enzymes and plasma ascorbic acid were significantly lower in power plants workers than in the control group ( p < 0.002). We can conclude that levels of mercury, arsenic and cadmium in blood, despite their concentration within the reference values, significantly affect plasma ascorbic acid concentration, superoxide dismutase and glutathione peroxidase activity, which are able to increase the risk of oxidative stress.